Regulation of soil nitrogen spatiotemporal variation by sprinkler irrigation patterns under surface fertilizer application - Rui Chen; Xiaofang Chen; Jian Wang; Xin Guo; Hong Li (Agricultural Water Management)
Efficient irrigation scheduling and optimal management of nitrogen (N) fertilizer application improve N use efficiency while reducing runoff and nitrate leaching risks. This study developed a COMSOL numerical model incorporating time-dependent nonuniform infiltration boundaries to investigate soil water-nitrogen dynamics under sprinkler irrigation after surface fertilizer application. Validated by soil tank experiments, the model assessed impacts of irrigation uniformity, strategy (continuous and intermittent), and fertilization amount (Fa) on soil water and nitrate transport characteristics, nitrate leaching risk, and nitrate distribution uniformity. Results show that according to the vertical distribution characteristics of water and nitrogen in the soil profile, nitrate leaching risk depended primarily on water application rate and irrigation duration rather than Fa. Intermittent irrigation enhanced lateral water redistribution, improved the uniformity of soil water content distribution, but reduced the uniformity of soil nitrate concentration distribution. As the uniformity coefficient of sprinkler irrigation (CUi) increased, the uniformity coefficients of soil water content distribution (CUsw) and nitrate concentration distribution (CUsn) also increased. When CUi was 40 %, the CUsw and CUsn were greater than 94 % and 15 % under intermittent sprinkler irrigation, while those were greater than 88 % and 39 % under continuous irrigation. Notably, intermittent strategies reduced vertical nitrate transport distance by 43.18 % compared to continuous irrigation, mitigating leaching risks. While CUsw consistently exceeded CUi due to soil moisture redistribution, optimal CUsn required CUi > 60 % for continuous and > 80 % for intermittent systems. The results establish a water application rate threshold of 30 mm h−1 and a maximum duration of 2.7 h for silty clay loam to prevent environmental contamination. This modeling framework enables precision irrigation scheduling that could enhance N-use efficiency while protecting groundwater ecosystem, recommending intermittent sprinkler irrigation after surface N fertilizer application for sustainable water-fertilizer management.